Design Automation for Embedded Systems An International Journal - Bergamaschi, Reinaldo A.; Rosenstiel, Wolfgang; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Embedded (electronic) systems have become the electronic engines of modern consumer and industrial devices, from automobiles to satellites, from washing machines to high-definition TVs, and from cellular phones to complete base stations. These embedded systems encompass a variety of hardware and software components which implement a wide range of functions including digital, analog and RF parts. Although embedded systems have been designed for decades, the systematic design of such systems with well defined methodologies, automation tools and technologies has gained attention primarily in the last decade. Advances in silicon technology and increasingly demanding applications have significantly expanded the scope and complexity of embedded systems. These systems are only now becoming possible due to advances in methodologies, tools, architectures and design techniques. Design Automation for Embedded Systems is a multidisciplinary journal which addresses the systematic design of embedded systems, focusing primarily on tools, methodologies and architectures for embedded systems, including HW/SW co-design, simulation and modeling approaches, synthesis techniques, architectures and design exploration, among others. Design Automation for Embedded Systems offers a forum for scientist and engineers to report on their latest works on algorithms, tools, architectures, case studies and real design examples related to embedded systems hardware and software. Design Automation for Embedded Systems is an innovative journal which distinguishes itself by welcoming high-quality papers on the methodology, tools, architectures and design of electronic embedded systems, leading to a true multidisciplinary system design journal.
Keywords: Special purpose computers; Computer-aided engineering; Electronic circuits; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design; Special Purpose and Application-Based Systems